Attention to L2 morpho-syntactic form across visual and aural modalities and the modulation of working memory: ERP evidence - Zhuang, Binyuan; Hu, Shuting; Liang, Lijuan (Journal of neurolinguistics, 2025)
The allocation of L2 learners’ attention to meaning and form across visual and aural modalities has been a critical area of research for decades. However, there is ongoing debate about whether L2 learners struggle to attend to both meaning and form simultaneously in the aural modality. This study investigates how L2 learners process morpho-syntactic form across these modalities when asked to read or listen for comprehension, and examines the modulatory role of working memory (WM). Thirty-four Chinese L2 learners of English with intermediate-high L2 proficiency completed story listening and reading comprehension tasks while ERP data was recorded, time-locked to the onset of the progressive marker “-ing”. Participants were unaware of 40 correct and 40 omitted uses of the marker. They also completed tasks assessing executive, phonological, and visuospatial WM. Linear mixed-effects models revealed that: (1) In the visual modality, syntactic violations elicited larger anterior negativity (AN) than correct forms within 300–500 ms and 500–800 ms, while in the aural modality, syntactic violations did not induce significant changes in ERP deflections compared with correct forms in the same time windows; (2) A significant interaction between Syntactic Correctness, executive WM and visuospatial WM was found only in the visual modality within 300–500ms. While Participants with high executive WM showed early ERP responses to syntactic violations, participants with low executive WM showed similar patterns only when their visuospatial WM was high. These findings suggest that L2 learners could attend to form in the visual modality, whereas such sensitivity may be less observable in the aural modality under the present experimental conditions. Moreover, visuospatial WM and executive WM interactively influence the early detection of morpho-syntactic features in the visual input. •This study examines how L2 learners process form across visual and aural modalities.•Visual violations showed larger AN than correct forms within 300–500 and 500–800 ms.•Aural violations may not cause significant changes in ERP deflections.•L2 learners can attend to form when reading in visual modality but not in the aural.•Visuospatial and executive WM influence morpho-syntactic detection in visual input.